Kebersihan Dalam Prespektif Hadis: Studi Analisis Kebersihan Di Sekolah Dasar Karang Sari Kecamatan Medan Polonia - Rustandi, Oky Akmal; Amir, Sulaiman Muhammad (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
In the context of Islamic teachings, the values of cleanliness play an important role and these guidelines are found in the teachings of the Qur'an and hadith, so that humans are ordered to maintain cleanliness. In this study, the focus of the researcher is how the application of hygiene values based on the teachings of the hadith at SD Karang Sari Polonia and how students and teachers understand the hadith of hygiene. The purpose of this research is to find out the application of hygiene values based on the teachings of the hadith at Karang Sari Elementary School, and to find out the understanding of students and teachers towards the hadith of hygiene. The method used in this research is qualitative method, then data collection techniques through observation, in-depth interviews and documentation studies. The research used the hadith approach. Based on the results of the study, the application of hygiene values at SD Karang Sari Polonia can make a significant contribution to environmental cleanliness and student hygiene. SD Karang Sari has implemented the hadith curriculum and every day they do cleaning activities so that the school environment remains comfortable when used for learning, therefore SD Karang Sari has implemented hygiene values based on hadith. The understanding of teachers and students of Karang Sari Elementary School towards cleanliness in the perspective of hadith is sufficient both in text and substance.